Philosophical and Pedagogical Preconditions and Development Algorithm of the Ascent from the Abstract to the Concrete in V. V. Davidov's Didactics (Continued) - N. K. Chapayev (Russian State Vocational Pedagogical University, 2015)
The second part of the paper denotes the significant philosophical and pedagogical problems related to implementation of V. V. Davydov's method of ascent from the abstract to the concrete, referred to as the basic concept of developmental education. Analyzing the potential and advantages of the above method along with the development technologies, the author gives the positive interpretation of traditional developmental education in the context of contemporary educational processes, and demonstrates its universality and thenecessity for further extension fare beyond the primary school limits. The paper contrasts the depth psychology, oriented on inner unconscious psychic processes and regarded as pedagogical basis (V. P. Zinchenko), and the vertex psychology focused on self-realization opportunities (L. S. Vygotsky, V. Frankl). The author regards the vertex psychology, addressing the spirit and intelligence, as the possible way out of educational crisis.The concept of developmental education aimed at fostering the students' cognitive abilities and humanistic attitude can contribute significantly to the educational process.